Pengaruh Penerapan Teori Belajar Sibernetik Terhadap Kemampuan Mahasiswa Mengelola Pembelajaran Berbasis Digital - Telaumbanua, Arozatulo; Gulo, Detiriani; Lahagu, Lisman Apriliani; Gulo, Citra Kurnihati; Gulo, Ener Kenangan Kasih (PT. Bangun Harapan Bangsa, 2022)
The development of increasingly sophisticated technology creates a learning atmosphere that must adapt. Students adapt to digital-based learning, both subject matter and assignments to be received and sent. Students can improve skills in managing learning and assignments digitally. Not a few students have not been able to professionally manage digital-based learning and assignments. Limited knowledge and infrastructure are important factors in the lack of student’s ability to manage their digital-based assignments. In addition, the lack of involvement of lecturers using digital-based learning also makes one of the weak abilities of students to adapt to managing electronic assignments. Therefore, this study uses a quantitative methodology with the aim of finding out how much influence the application of cybernetic learning theory has on students' ability to manage digital-based assignments. To deal with this problem, the researchers provide a solution by conducting training and technical guidance to students on the use of technology in learning and seeking to procure facilities and infrastructure that support digital-based learning processes.